Evaluation of nutritional, functional and sensory properties of breadnut seed flour (Artocarpus camansi) as a substitute for wheat flour in pandesal bread - Ayudtud, Levi Joy, B.
The challenges of wheat cultivation in the Philippines' tropical climate and reliance on wheat importation calls for the development of alternative flours thus, this study explored breadnut seed flour (BSF) as a partial substitute for wheat flour in pandesal. The nutritional, functional, and sensory properties of BSF at substitution levels of 5%, 15%, and 50% were evaluated. The ash and fat content of the wheat-breadnut seed flour (WBSF) blends significantly increased (p<0.05) while carbohydrate content significantly decreased (p<0.05) as BSF level increased. Additionally, protein content did not show significant differences across all WBSF blends and to the control. In general, the WBSF blends did not differ (p<0.05) in terms of water absorption capacity (WAC), water solubility index (WSI), swelling power, emulsion activity, and emulsion stability with B50 having the significantly (p<0.05) highest WSI. A 50% substitution of breadnut flour for wheat flour led to a significant (p<0.05) decrease in foaming capacity and stability. Pandesal samples up to 15% BSF substitution for wheat flour were generally acceptable, with 5 % substitution showing no significant difference (p>0.05) compared to the control. Overall, BSF showed potential in enhancing the nutritional profile of baked goods, with up to 15% level substitution for wheat flour with minimal impact on functional properties except for foaming capacity and stability.